Rome and Environs : an Archaeological Guide. - Coarelli, Filippo (University of California Press, 2014)
This superb guide brings the work of Filippo Coarelli, one of the most widely published and well-known scholars of Roman topography, archeology and art, to a broad English-language audience. Conveniently organized by walking tours and illustrated throughout with clear maps, drawings, and plans, Rome and Environs: An Archaeological Guide covers all of the major, and an unparalleled number of minor, ancient sites in the city, and, unlike most other guides of Rome, includes major and many minor sites within easy reach of the city, such as Ostia Antica, Palestrina, Tivoli, and the many areas of in.